Biofilm Formation in Dairy: A Food Safety Concern—Insights into the prevalence of Pseudomonadota and yeasts on milking system surface biofilms - Mérilie Gagnon; Samuel Jean; Juan de Toro-Martín; Gisèle LaPointe; Évelyne Guévremont; Simon Dufour; Denis Roy (Journal of Dairy Science, 2025)
ABSTRACT: Biofilms pose major challenges to milk quality and safety, yet their composition in the dairy environment remains under-characterized. This study investigated the prevalence and composition of biofilms on milking system surfaces in commercial dairy farms, focusing on Pseudomonadota, a dominant phylum in raw milk. We sampled bulk tank raw milk (BTRM), tap water, and milking equipment surfaces after cleaning from 20 dairy farms in Québec, Canada, using S1 milk agar, specifically designed to target Pseudomonadota through a culturomics approach. A total of 474 colonies were selected and identified by MALDI-TOF MS. Results demonstrated the presence of multispecies biofilms, within the phylum of Pseudomonadota, including potential spoilage and pathogenic bacteria, such as Pseudomonas aeruginosa. Furthermore, the study revealed a significant presence of yeasts (42% of the isolates), predominantly Candida parapsilosis. Biofilms were predominantly detected in milk pipelines and milking machines (milk pipeline: 5.42 log gene copy number/swab; milking machine: 5.16 log gene copy number/swab), with greater bacterial loads quantified by quantitative PCR in fall than spring or summer. Partial least squares discriminant analysis revealed that the microbial composition of biofilms differed from that of BTRM (classification error rate: 0.23 and area under the curve: 0.95), although several species were shared, such as Candida parapsilosis and P. aeruginosa, and Escherichia coli. Tap water was not identified as a major contamination source of Pseudomonadota for dairy biofilms as only 2 species were shared across water, BTRM, and biofilm samples (Pantoea agglomerans and Serratia liquefaciens). The presence of these biofilms, harboring potentially pathogenic and spoilage microorganisms, poses a challenge to milk quality and safety. These findings provide data on the diversity of culturable Pseudomonadota and yeasts in biofilms on dairy farms and highlight the need for improved sanitation practices to mitigate microbial contamination in milk production.